2022
DOI: 10.51585/gjvr.2022.1.0028
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of an outbreak of brucellosis in a mixed dairy farm and evaluation of a test and slaughter strategy to release the herd out of the quarantine

Abstract: An outbreak of brucellosis in a mixed dairy farm with 508 animals (370 cows, 120 sheep, and 18 camels) at Fayoum governorate, North Upper Egypt, was investigated. A storm of abortion and several cases of retained placenta were reported among cows and ewes in April 2020. Serodiagnosis of brucellosis was done using Rose Bengal Test (RBT) and Buffered Acidified Plate Antigen Test (BAPAT). The Milk Ring Test (MRT) was applied to the milk of seropositive animals. A total of 89 samples were used for isolation of Bru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 57 publications
1
9
0
Order By: Relevance
“…The control strategies for livestock brucellosis are different from region to region depending on available disease prevalence in each region. It has been well documented that test and slaughter strategy (El‐Diasty et al., 2022) and vaccination are among the most effective methods used in controlling and preventing animal brucellosis in endemic regions (El‐Diasty et al., 2022; Hou et al., 2019). Four vaccines, S2, RB51, S19, and Rev1, are available to control brucellosis due to B. abortus infections in bovids and B. melitensis in small ruminants (Hou et al., 2019; Lalsiamthara & Lee, 2017; Zhu et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The control strategies for livestock brucellosis are different from region to region depending on available disease prevalence in each region. It has been well documented that test and slaughter strategy (El‐Diasty et al., 2022) and vaccination are among the most effective methods used in controlling and preventing animal brucellosis in endemic regions (El‐Diasty et al., 2022; Hou et al., 2019). Four vaccines, S2, RB51, S19, and Rev1, are available to control brucellosis due to B. abortus infections in bovids and B. melitensis in small ruminants (Hou et al., 2019; Lalsiamthara & Lee, 2017; Zhu et al., 2016).…”
Section: Resultsmentioning
confidence: 99%
“…There are few valid data on the actual prevalence of brucellosis in ruminant livestock of the Middle Eastern countries available (Benkirane, 2006). Different studies showed that older animals and mixed farming systems of small ruminants were significantly associated with a higher prevalence of brucellosis (Abdelbaset et al., 2018; Dadar et al., 2021; El‐Diasty et al., 2022; Samaha et al., 2009). Furthermore, few studies showed that a higher risk of brucellosis is associated with exposure to abortive animals and recently calved animals (Hotez et al., 2012; Musallam et al., 2016; Pappas & Memish, 2007).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Egypt's brucellosis control programmes have used two approaches: vaccination to susceptible animals and slaughter of the positive serologic cases. The test-and-slaughter strategy, as well as mass vaccination of animals, continue the most applied methods for controlling brucellosis in endemic countries (Vatankhah et al, 2019;El-Diasty et al, 2022). As a result, ongoing research is critical to preventing transmission and identifying new reservoir areas (Zameer Durrani et al, 2020).…”
Section: Internal Medicine and Infectious Diseasementioning
confidence: 99%
“…Serological diagnosis of Brucella on serum samples was performed through Rose Bengal Test (RBT) and Buffered Acidified Plate Antigen Test (BAPAT), while milk ring test (MRT) in milk is still our first choice to catch the positive cases. MRT, RBT, and BAPAT are the most prevalent screening serological tests but eradication programs can't depend on MRT alone because little titer of antibodies in milk and factors of fat collecting lead to decrease its sensitivity [13,14]. MRT not only be used in bulk milk samples analysis but used also to test the individual milk samples.…”
Section: Introductionmentioning
confidence: 99%